1001 symmetrical patterns : a complete resource of pattern designs created by evolving symmetrical shapes - Friedenberg, Jay.; Roesch, Jacob (Beverly : Rockport Publishers, 2010)
Artists, graphic designers, and craftspeople are always looking for new sources of inspiration and new ideas to incorporate into their work. This book is an extensive print and electronic library of symmetrical patterns in changing arrangements and colorways, inspired by traditional iconic motifs found in various cultures throughout history. The patterns are suited to many applications, including quilt, tile, fabric, jewelry, architectural, product, website, and graphic design. The enclosed CD-ROM allows the reader to reproduce, resize, or otherwise modify all of the designs for his or her own purposes.
Keywords: Repetitive patterns (Decorative arts); Symmetry (Art)